Marginalisation and Restructuring in Nigeria: An Exploration - Omemma, Dilichukwu A. (SOUTH EAST JOURNAL OF POLITICAL SCIENCE, 2021)
The ferment associated with the renewed clamour for the restructuring of the Nigerian State tends to be snowballing into the “yugoslavisation” of the country. This is a product of the morass of nationhood and identity crisis confronting the country since its creation. Consequently, there has been a cacophony of prescriptions considered as a desideratum to lead the country out of the path of disintegration. For instance, while a section of the country advocates true federalism based on fiscal autonomy of the constituent parts, others largely from the southeastern axis of the country insist on loose union anchored on confederation. On their part, the position of the south-south region of the country is that the framework for the continued existence of the Nigerian State is resource control. All these divergent views however, converge on the restructuring maxim, which the northern part of the country is stoutly opposed to on the grounds that there was nothing wrong with the structure of the Nigerian State as presently constituted. The conservative temperament of the north has continued to exacerbate the acrimonious rancour and agitation for self-determination amongst most of the southern part as a panacea to their marginalization in all facets of the scheme of things in the Nigerian State. This is an exploratory study aimed at interrogating the source(s) of the agitation for restructuring with a view to finding a viable path to addressing the debilitating grievances amongst the constituent parts of the Nigerian State. Both primary and secondary sources were utilized in generating data while the triple balancing theory was adopted as a framework for managing the political miasma of the national question in Nigeria.